Surface Co-presentation of BMP-2 and integrin selective ligands at the nanoscale favors α5β1 integrin-mediated adhesion. (January 2021) - Posa, Francesca; Baha-Schwab, Elisabeth H.; Wei, Qiang; Di Benedetto, Adriana; Neubauer, Stefanie; Reichart, Florian; Kessler, Horst; Spatz, Joachim P.; Albiges-Rizo, Corinne; Mori, Giorgio; Cavalcanti-Adam, Elisabetta Ada
Abstract: Here we present the use of surface nanopatterning of covalently immobilized BMP-2 and integrin selective ligands to determine the specificity of their interactions in regulating cell adhesion and focal adhesion assembly. Gold nanoparticle arrays carrying single BMP-2 dimers are prepared by block-copolymer micellar nanolithography and azide-functionalized integrin ligands (cyclic-RGD peptides or α5 β1 integrin peptidomimetics) are immobilized on the surrounding polyethylene glycol alkyne by click chemistry. Compared to BMP-2 added to the media, surface immobilized BMP-2 (iBMP-2) favors the spatial segregation of adhesion clusters and enhances focal adhesion (FA) size in cells adhering to α5 β1 integrin selective ligands. Moreover, iBMP-2 copresented with α5 β1 integrin ligands induces the recruitment of αv β3 integrins in FAs. When copresented with RGD, iBMP-2 induces the assembly of a higher number of FAs, which are not affected by α5 β1 integrin blocking. Our dual-functionalized platforms offer the possibility to study the crosstalk between integrins and BMP receptors, and more in general they could be used to address the spatial regulation of growth factors and adhesion receptors crosstalk on biomimetic surfaces. Graphical abstract: Image 1